Placental growth factor in suspected preterm pre‐eclampsia: a review of the evidence and practicalities of implementation. (26th August 2020) - Hurrell, A; Beardmore‐Gray, A; Duhig, K; Webster, L; Chappell, LC; Shennan, AH
Abstract : Despite extensive research, the pathophysiology and prevention of pre‐eclampsia remain elusive, diagnosis is challenging, and pre‐eclampsia remains associated with adverse maternal and perinatal outcomes. Angiogenic biomarkers, including placental growth factor (PlGF) and soluble fms‐like tyrosine kinase 1 (sFlt‐1), have been identified as valuable biomarkers for preterm pre‐eclampsia, accelerating diagnosis and reducing maternal adverse outcomes by risk stratification, with enhanced surveillance for high‐risk women. PlGF‐based testing is increasingly being implemented in clinical practice in several countries. This review provides healthcare providers with an understanding of the evidence for PlGF‐based testing and describes the practicalities and challenges to implementation. Tweetable abstract: Placental growth factor in pre‐eclampsia: evidence and implementation of testing. Tweetable abstract: Placental growth factor in pre‐eclampsia: evidence and implementation of testing.